FIRM SIZE MEMODERASI MANAJEMEN LABA DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE - Fitri, Annisa; Margie, Lyandra Aisyah (LPPM Universitas Bina Bangsa, 2024)
This study aims to test and analyze the effect of earnings management and corporate social responsibility on tax avoidance with firm size as a moderating variable in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. This type of research is quantitative research using multiple linear regression analysis methods, using eviews12. The population in this study amounted to 123 companies, the sample selection used purposive sampling method so as to obtain 24 companies. The test results in this study indicate that simultaneously earnings management and corporate social responsibility have a significant effect on tax avoidance. Partially, corporate social responsibility has not significant effect on tax avoidance, while earnings management has no significant effect on tax avoidance. Firm size is able to moderate the relationship between corporate social responsibility and tax avoidance. However, firm size is not able to moderate the relationship between earnings management and tax avoidance